2022
DOI: 10.3390/bioengineering9110708
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rigid–Elastic Artery Wall of Carotid and Coronary Stenosis on Hemodynamics

Abstract: Cardiovascular system abnormalities can result in serious health complications. By using the fluid–structure interaction (FSI) procedure, a comprehensive realistic approach can be employed to accurately investigate blood flow coupled with arterial wall response. The hemodynamics was investigated in both the coronary and carotid arteries based on the arterial wall response. The hemodynamics was estimated based on the numerical simulation of a comprehensive three-dimensional non-Newtonian blood flow model in ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Blood, which in larger vessels contains both liquid and solid parts, exhibits a Newtonian flow state and a constant viscosity that changes according to the vessel diameter. Blood plasma, which is an incompressible, Newtonian-homogeneous fluid that makes up over 50% of blood [ 33 ], exhibits Newtonian behavior [ 25 ]. In microcirculatory systems, however, such as small vessels and capillaries with diameters under 1 mm, blood can be treated as a non-Newtonian fluid [ 38 ] whose changing viscosity can be determined using a modified Quemada model [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood, which in larger vessels contains both liquid and solid parts, exhibits a Newtonian flow state and a constant viscosity that changes according to the vessel diameter. Blood plasma, which is an incompressible, Newtonian-homogeneous fluid that makes up over 50% of blood [ 33 ], exhibits Newtonian behavior [ 25 ]. In microcirculatory systems, however, such as small vessels and capillaries with diameters under 1 mm, blood can be treated as a non-Newtonian fluid [ 38 ] whose changing viscosity can be determined using a modified Quemada model [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, this study assumed that the vessel walls in the patient-specific model were rigid, an assumption that led to minor differences in simulation results due to wall shear stress and the relative velocity of the wall, because blood in contact with the wall was not discussed, as in a previous study [ 30 ]. A rigid wall assumption has been included in the majority of computational flow studies [ 47 ], such as a 2022 investigation of the CFD simulation of the cardiovascular system by Albadawi et al [ 33 ], which concluded that assuming a rigid wall led to only slight differences when modeling large-diameter vessels. Since the iliac vein is relatively large in diameter, assuming a rigid wall seemed acceptable for the present model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Displacement and deformation of the computational domain were not measured directly from the CT images and were neglected to simplify the complexity and assess the accuracy of the proposed Gaussian process approached by comparing the reconstructed velocity to the CFD results. The displacement and deformation of the coronary artery will introduce additional sources of error [ 101 ] that may require further algorithm developments. In this study, we have performed a computational experiment on PEPT accuracy, flow recovery and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the CFD-based simulations are of high computational cost due to the requirements of mighty computing resources, large-scale computing time, and highly skilled experts (Yamaguchi et al, 2016;Fu et al, 2020). Moreover, the simulation is generally performed in a patient-specific manner by using the image-based geometric model for each individual under specific boundary conditions, which needs to be conducted for all patients and is usually highly time-consuming (Fu et al, 2010;Conti et al, 2016;Bluestein, 2017;Polanczyk et al, 2018;Albadawi et al, 2021). Thus, it is a crucial issue to pay the expensive computational costs for real-time simulations of complex blood flows in association with the realistic clinical applications of CFD methods for surgical treatments such as CAS.…”
Section: Introductionmentioning
confidence: 99%